Comet‐FISH studies for evaluation of genetic damage of citalopram in somatic cells of the mouse. Issue 9 (12th February 2013) - Attia, Sabry M.; Ashour, Abdelkader E.; Bakheet, Saleh A.
ABSTRACT: Damage to DNA can lead to many different acute and chronic pathophysiological conditions, ranging from cancer to endothelial damage. The present study was designed to evaluate the DNA damage of an antidepressant drug, citalopram, at the recommended human doses in somatic cells of mice in vivo . Mice exposed to citalopram at varying oral doses of 12 or 24 mg kg –1 for 7 days exhibited a significant increase in the level of DNA‐strand breaking and micronuclei formation as detected by a bone marrow comet assay and micronucleus test, respectively. Furthermore, using fluorescence in situ hybridization (FISH) analysis with the centromeric mouse‐satellite DNA‐probe for erythrocyte micronuclei it could be shown that citalopram is aneugen as well as clastogen in somatic cells in vivo . Colchicine (COL) and mitomycin C (MMC) were used as positive controls and these compounds produced the expected responses. Both the clastogenic and the aneugenic potential of citalopram can give rise to the development of secondary tumours and abnormal reproductive outcomes. Overall, the results suggest that citalopram at the recommended human doses induces some genetic alterations, which can adversely affect the normal cellular functioning in mice. The mechanism(s) by which citalopram cause this adverse effect appear related, in part, to primary DNA strand breakage as detected by the comet assay as well as clastogenic and aneugenic events as detected by the FISH assay. Therefore, the clinical use of citalopram must be weighed against the risks of genetic damages in citalopram users. Copyright © 2013 John Wiley & Sons, Ltd. Abstract : This study was designed to evaluate the genotoxicity of citalopram at the recommended human doses in somatic cells of mice. Mice exposed to citalopram at varying oral doses of 12 or 24 mg/kg for 7 days, exhibited significant increase in the level of DNA‐strand breaking and micronuclei formation. Furthermore, by FISH analysis with the centromeric DNA‐probe for erythrocyte micronuclei it could be shown that citalopram is aneugen as well as clastogen in somatic cells in vivo .